Optimizing Of Injection Moulding Process Parameters For Recycled Plastic Material Using Taguchi Method - Mehat, Nik Mizamzul (2010)
A large amount of plastic parts presently produced, makes it imperative to search for alternative for recycling or making use of these materials, since they are not biodegradable. Injection moulding, one of the most prevalent plastics processing techniques facilitates these recycled materials to be substituted for virgin material in producing plastic parts. However, the deterioration in mechanical properties of the part made of recycled plastic is the major drawback that limits the usage of recycled plastic. One of the foremost causes is variation in processing parameters. It is of critical importance to effectively control all the influencing processing parameters during the manufacturing process by an appropriate optimization method. Therefore, the main goal of conducting this research is to primarily investigate the effects of injection moulding parameters on the mechanical properties of plastic part made of recycled plastics in various of compositions.